Severe stenosis of the internal carotid artery is not associated with borderzone infarcts in patients randomised in the European Carotid Surgery Trial. - Hupperts, R; Warlow, C; Slattery, J; Rothwell, P (1997)
Borderzone infarcts are usually regarded as being caused by low cerebral blood flow distal to a severely stenosed or occluded artery, particularly the internal carotid artery. To explore this hypothesis we have related borderzone infarction, defined by CT both in the classical way and by taking into account the variable extent of the territory of the blood supply of the cerebral arteries, to the severity of any disease of the symptomatic artery in 384 patients in the European Carotid Surgery Trial in whom a scan showing infarction was available. Although there was a tendency for borderzone infarction to occur more often distal to severe carotid disease, this was not significant, and many cases of borderzone infarcts occurred in patients with mild or moderate carotid disease. Therefore, the topography of infarction on CT cannot be used to imply a particular pathophysiology based on the severity of disease of the artery supplying that area of the brain. Severe carotid stenosis is neither sufficient nor necessary to produce borderzone infarction. However, it has to be emphasized that patients with carotid occlusion are not included in this study.